PERFORMANCE OF MODULUS RESILIENT AND PERMANENT DEFORMATION FROM ASPHALTIC CONCRETE WEARING COURCES (AC-WC) MIXED LINES AND DANCE GRADED EMULSION MIXES (DGEM) TYPE III AND TYPE IV USING ASPHAL EMULSI TYPE CSS-1H - MULYANA - NIM : 26914320, SUBHAN
Flexible pavement types used in Indonesia in general using hot mix asphalt. Beginning around the 1990s for road works in Indonesia started using emulsion asphalt. The main objective of this study was to examine the performance of Cold Asphalt Emulsion mixture (DGEM) type III and type IV using CSS-1h emulsion asphalt with asphaltic concrete wearing cources (AC-WC). Characteristic of aggregate crushed stone, asphalt and performance of mixed Marshall characteristics, Marshall Immersion, Resilient Modulus, Permanent Deformation and Modulus of Elasticity. The result of Marshall characteristic test on the mixture of DGEM type III and type IV using CSS-1h shows that both of the DGEM mixture are close to the stability value of the AC-WC mixture. For Resilient Modulus test results with UMATTA tool on cold asphalt mixture can not be tested because of weakness. Permanent Deformation testing with WTM at 45oC DGEM type III underwent a depreciation of 2.97 mm and DGEM IV underwent a deponent of 3.47 mm. While in pungujian with ITS tool, DGEM either type III or type IV has a modulus of elasticity 50% smaller than the Modulus of Elasticity of AC-WC mixture. From Marshall testing and Permanent Deformation DGEM type III is better than DGEM type IV, but in DGEM type IV Elastic Modulus is better than DGEM type III. The results of DGEM type III and type IV testing using CSS-1h emulsion asphalt at certain asphalt content resulted in Marshall stability approaching the asphaltic concrete wearing cources so that DGEM type III and type IV using CSS-1h emulsified asphalt could be used in moderate traffic.